Gut-tropic α4β7+CD8+ T cells contribute to pancreatic β cell destruction in type 1 diabetes - Su, Zhangyao; Bian, Lingling; Zhao, Hang; Cai, Yun; Yang, Tao; Li, Shushu; Xu, Xinyu (Frontiers in Immunology, 2025)
BackgroundT cells are crucial in destroying pancreatic β cells, resulting in insulitis in type 1 diabetes (T1D). However, only 1% to 2% of infiltrating CD8+ T cells are specific for islet autoantigens. The mechanisms driving non-cognate T cells to the islets and their potential pathogenic roles remain unclear.MethodsWe analyzed the frequency and function of circulating gut-tropic immune cells in 99 patients with T1D and 57 healthy controls. We also analyzed single-cell RNA sequencing on pancreata from 10 T1D donors, 11 autoantibody-positive donors, and 15 non-diabetic controls. Correlation analysis was performed to elucidate the relationship between gut-tropic cells and clinical variables. In NOD mice, we examined gut-tropic T cell frequencies, cytokine profiles, and cytotoxicity at different disease stages. Additionally, we investigated the role of integrin α4β7 on gut-tropic T cells function and migration.ResultsGut-tropic CD8+ T cells are reduced in peripheral blood but elevated in pancreatic islets of patients with T1D, correlating with impaired β-cell function. Gut-tropic CD8+ T cells exhibited stronger cytokine production than non-gut-tropic counterparts. In NOD mice, gut-tropic cells increased in the islets and decreased in the blood during insulitis progression. Gut-tropic CD8+ T cells showed augmented cytokine production and cytotoxicity against islet cells. Integrin α4β7 was a key mediator of the pathogenicity of CD8+ T cells and upregulated by the inflammatory signals. Insulitis directly drove gut-tropic CD8+ T cells migrating to inflamed islets.ConclusionsGut-tropic CD8+ T cells bridge the intestinal immune system and the pathogenesis of T1D, offering potential biomarkers and therapeutic targets.